The Role of Islamic Religious Education in Building Awareness of Sustainable Development Goals (SDGs): A Systematic Literature Review - Giyarsi, Giyarsi; Saputra, Adi; Fadilah, Siti; Puspitarani, Nafa; Khajar, Ratna (International Journal on Advanced Science, Education, and Religion, 2025)
This study examines the role of Islamic Religious Education in building awareness of Sustainable Development Goals (SDGs) through a systematic literature review approach. The research aims to identify the contributions of Islamic Religious Education toward sustainability awareness, analyze dominant themes within recent scholarly discussions, and explore how Islamic educational values support the achievement of SDGs. The study employed a qualitative systematic literature review method by collecting and analyzing academic publications published between 2020 and 2026 from reputable scholarly databases and journals. The selected literature was screened based on relevance, credibility, and thematic suitability concerning Islamic education and sustainable development. A total of 32 academic works were analyzed using thematic analysis to identify recurring concepts and research trends. The findings reveal that Islamic Religious Education significantly contributes to sustainability awareness through environmental ethics, religious moderation, character education, social responsibility, and curriculum transformation. Islamic teachings such as khalifah (stewardship), justice (‘adl), moderation (wasatiyyah), and compassion (rahmah) were found to align closely with the principles of sustainable development. The review also indicates that Islamic educational institutions increasingly integrate sustainability-oriented values into educational practices, environmental programs, and social engagement activities. However, the study identified challenges related to limited empirical implementation and the dominance of conceptual approaches within existing research. This study contributes to the growing discourse connecting Islamic education and sustainable development by providing a comprehensive synthesis of recent literature and highlighting the strategic role of Islamic Religious Education in promoting environmentally conscious, socially responsible, and ethically grounded global citizens.